PENGENAAN SUBSIDI BAJA NIRKARAT PRODUKSI INDONESIA DALAM PUTUSAN UNI EROPA DITINJAU DARI HUKUM PERDAGANGAN INTERNASIONAL: The Imposition of Subsidies on Indonesian Stainless Steel Production in the European Union Decision in View of International Trade Law - Agung Wijaya; Saleh, Rosdiana (AMICUS CURIAE, 2025)
Subsidies are given with the aim of supporting the export performance of a country and promoting welfare, especially for developing countries. Subsidy regulation refers to the rules of the GATT and WTO Agreement. GATT has regulated subsidies in Article XVI of GATT, while the WTO Agreement that regulates subsidies is the SCM Agreement. Article XVI of GATT stipulates that subsidies provided by developing countries for economic improvement cannot be sanctioned in the form of countervailing duty. The problem is whether the subsidization of stainless steel products produced in Indonesia and exported to the European Union violates or does not violate the rules of the GATT / WTO Agreement? This research is a normative and descriptive research to examine the subsidies as argued by the European Union. Secondary data becomes the main data which is processed qualitatively and then collected through literature study. Finally, deductive conclusions are drawn from the analysis that has been done. Indonesia's policy regarding stainless steel does not violate the rules of the GATT / WTO Agreement so that the imposition of sanctions by the European Union is not in accordance with the rules of international trade law.